ANALISIS KELAYAKAN BISNIS PENGEMBANGAN UMKM SPICYPEDIA DALAM PERSAINGAN BISNIS - Era Deka, Rio; Dwi Evasoyaningrum, Irlina; Dwi Pratiwi, Novita; Vidia Fransisca, Dea; Artika Sari, Helmi; Maulinda, Imelda; Aprillia Salsabila, Nadya (JAMBIS : Jurnal Administrasi Bisnis, 2024)
The purpose of this study is to determine the business feasibility of the Spicypedia UMKM. The method used in this study is qualitative and quantitative with an analysis of 7 aspects of business feasibility studies which include legal aspects, marketing aspects, technical aspects, sosial economic aspects, management/organizational aspects, environmental aspects and financial aspects. The technique of collecting data in this study is by observing objects at the company, documentation, and direct interviews with the parties concerned. The results of the analysis of the legal aspects stated that it was not yet feasible, while for the other 6 aspects it showed positive results that the business being carried out by the Spicypedia MSME was feasible to do.